Malnutrition among Pediatric Cancer Patients: A Study of Government Hospitals in Delhi - Singh, Amitabh; Mandal, Piali; Bagai, Poonam; Fatima, Nikhat; Sharma, Khushboo; Gupta, Haresh; Sharma, Pooja; Singh, Padam; Keshari, Adarsh (Indian Journal of Medical and Paediatric Oncology, 2025)
Research indicates a considerably higher incidence of malnutrition at the time of diagnosis among patients with pediatric cancer. Studies have also shown that malnutrition tends to worsen with anti-cancer therapies. However, there are limited studies conducted in the Indian context, and those available often involve small sample sizes.This study aims to address this gap by analyzing data of patients with pediatric cancer treated at two government hospitals in Delhi.This retrospective study includes data from 1,042 patients with pediatric cancer, collected over 6 years from April 2018 to April 2024. The dataset includes age at diagnosis, cancer type, and anthropometric measurements recorded at the initial contact. The analysis focuses on the prevalence of malnutrition, stratified by gender, age group, and cancer type.Among patients with pediatric cancer, more than 80% were diagnosed with hematological malignancies. This study identified an overall malnutrition prevalence of 39.7% (414 out of 1,042). Notably, the prevalence increases with age.Given the substantially higher levels of malnutrition among patients with pediatric cancer at baseline and the anticipated increase during anticancer therapy, there is a pressing need for close monitoring and the development of targeted, individualized nutritional interventions. Such measures are essential to mitigate the impact of malnutrition on treatment outcomes and quality of life.
Keywords: malnutrition; incidence; pediatric cancer; WHO norms; acute lymphoblastic leukemia; prevalence